2013
DOI: 10.1002/srin.201200210
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Dissolution Mechanism of Sulfur in CaMnSilicate Melts: Structural View

Abstract: The sulfide capacities of the CaO-SiO 2 -MnO(-Al 2 O 3 -MgO) slags were measured at 1873 K over a wide composition range using a gas-slag equilibration method. The effects of MnO content and the MnO $ CaO substitution on the sulfide capacity of molten slag were also investigated based on the structural view of silicate melts. In the multicomponent silicate melts containing high MnO (up to about 50 wt%), the sulfide capacity mainly increased with increasing MnO content. Also, the sulfide capacity and the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The organic relationships between the silicate structure and the thermodynamic properties of oxide melts such as the mixing free energy of silicates and sulfide capacity have been reported. 10,11) In particular, Park 12,13) demonstrated that the sulfide capacity is strongly affected by the structure of the CaO-SiO 2 -MnO system, and that the excess free energy of MnO is inversely proportional to the degree of polymerization by employing Raman spectra analysis in conjunction with a computational thermodynamic assessment. Therefore, the influence of the silicate structure on the activity coefficient of MnO should be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The organic relationships between the silicate structure and the thermodynamic properties of oxide melts such as the mixing free energy of silicates and sulfide capacity have been reported. 10,11) In particular, Park 12,13) demonstrated that the sulfide capacity is strongly affected by the structure of the CaO-SiO 2 -MnO system, and that the excess free energy of MnO is inversely proportional to the degree of polymerization by employing Raman spectra analysis in conjunction with a computational thermodynamic assessment. Therefore, the influence of the silicate structure on the activity coefficient of MnO should be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The sulfide capacity increases by increasing the MnO/CaO ratio at a fixed silica content which is greater than about 30 wt%, whereas it decreases by increasing the MnO/CaO ratio at silica content lower than about 30 wt%. 23,24) The critical SiO 2 content is about 30 wt% based on the competitive dissolution mechanism of sulfur in Ca-Mn-silicate melts. The used SiO 2 content in the calculation is 33 wt% and so the effects of MnO and CaO are similar in the present slag system.…”
Section: Effect Of Mnomentioning
confidence: 99%